If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.5(y + 8) = 2(y + -1) Reorder the terms: 0.5(8 + y) = 2(y + -1) (8 * 0.5 + y * 0.5) = 2(y + -1) (4 + 0.5y) = 2(y + -1) Reorder the terms: 4 + 0.5y = 2(-1 + y) 4 + 0.5y = (-1 * 2 + y * 2) 4 + 0.5y = (-2 + 2y) Solving 4 + 0.5y = -2 + 2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2y' to each side of the equation. 4 + 0.5y + -2y = -2 + 2y + -2y Combine like terms: 0.5y + -2y = -1.5y 4 + -1.5y = -2 + 2y + -2y Combine like terms: 2y + -2y = 0 4 + -1.5y = -2 + 0 4 + -1.5y = -2 Add '-4' to each side of the equation. 4 + -4 + -1.5y = -2 + -4 Combine like terms: 4 + -4 = 0 0 + -1.5y = -2 + -4 -1.5y = -2 + -4 Combine like terms: -2 + -4 = -6 -1.5y = -6 Divide each side by '-1.5'. y = 4 Simplifying y = 4
| 7+8q=7q | | H=-16t^2+24t+40 | | -2x-1=2x+15 | | n/-12.168=-2 | | z+iz+1=0 | | 12(n+8)=132 | | 10(x+3)-9x-4=x-5+3 | | 4x-15=7x-60 | | (7x+15)=8x | | 2(x-4)=35 | | 3/r=12/17 | | y=(7+5k)x | | 4x^2+28x^3=0 | | 3k-5=7k+7 | | 2a+9=22249 | | 4x-31+2x=11 | | ln(3.2)=x | | 2(c+6)=c-13 | | 7y-8+6y+1= | | 13x+8-10x=65 | | x/-6=1-(-4) | | 4x+y+2xy+6y-2x= | | logx(3x-1)=0 | | 7/2=91/x | | 6-y=-y+2 | | (xy)dx=(1+x^2)dy | | 12-6r=2r+36 | | 12-5=x/4 | | 6x-15-x=65 | | 1/5x-9/10x=10-31 | | 10=s-2 | | 7+(3)= |